Spectral analysis of peri-pharyngeal muscles’ EMG in patients with OSA and healthy subjects - Oliven, Ron; Cohen, Guy; Somri, Mostafa; Schwartz, Alan R.; Oliven, Arie (Respiratory physiology & neurobiology, 2019)
•Dyscoordination of dilator muscles during sleep contributes to pharyngeal collapse.•We found a sleep-dependent shift in peri-pharyngeal muscles power spectrum.•This finding suggests a state-dependent alteration in dilators motor unit activation.•We speculate that this change may lessen dilator muscles’ mechanical efficiency. In addition to dyscoordination of upper airway dilator muscles activity, sleep may also alter the pattern of intra-muscular activation of single motor units (SMUs). Such changes should be identifiable by a state dependent change in EMG power spectrum, i.e., a shift in centroid frequency (ƒc) during sleep. EMGs of the genioglossus and four other peri-pharyngeal muscles were recorded in OSA patients (n = 8), age-matched healthy subjects (n = 7), and 5 young healthy subjects, and ƒc was calculated for wakefulness and sleep periods. ƒc decreased with the onset of sleep and returned to baseline levels after arousal. ƒc of all muscles decreased similarly and significantly during sleep in the OSA and the age-matched healthy subjects, but not in the young subjects. The pattern of decrease in ƒc is compatible with altered synchronization of SMUs during sleep. We speculate that these changes may contribute to the failure of dilator muscles to improve flow limitation during sleep in older subjects.